Faktor- Faktor Yang Mempengaruhi Profitabilitas Bank - Wijayanti, Langgeng, Imronudin, SE,MSi, Ph.D (2017)
The purpose of this study is to analyze the effect of the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Operating Expenses to Operating Income (BOPO) to Profitability (ROA) of National Private Banks in Indonesia in 2013-2015. The population of this study is National Commercial Bank that are listed on the Indonesia Stock Exchange in 2013-2015. The samples used were 19 National Commercial Bank listed on the Indonesia Stock Exchange, Purposive Sampling method was used to select the sampel. To test propoced hypothesis, this research used multiple regression analysis. The results based on partial hypothesis test (t-test) showed that the CAR and LDR variable do not affect the bank's profitability while variable NPL, NIM and BOPO significantly effect the bank profitability. The result of the coefficient of determination (R2) obtained R Square of 0.916, this shows that the profitability of banks can be explained by the variable CAR, NPL, NIM, LDR and ROA of 91.6%, while 8.4% are influenced by other factors outside variables studied.